Hemodynamic impairment of double culprit ST elevation myocardial infarction, double the trouble: a case report - Mikhael Asaf; Jonathan Edbert Afandy; Siska Suridanda Danny (The Indonesian Heart Association, 2026)
In “Hemodynamic impairment of double culprit ST elevation myocardial infarction, double the trouble: a case report” (Indonesian Journal of Cardiology, 46(2), 80-88. https://doi.org/10.30701/ijc.1791), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1791. The error occurs only in the PDF; the DOI listed in the article metadata is already correct. The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1791